A Review on the Status of Determinants in Tourism Policy - Kaini, Tika Raj; Gautam, Sahadev; Thapa, Asim (NUTA Journal, 2022)
This article analyzes the settings, conditions, and practices of tourism policy through descriptive and analytical methods. One important area of Nepali public policy is tourism. Government is the body responsible for developing, implementing, and gathering feedback on new and updated tourist policies. One of the key components of tourism is the private sector. The distinction is that while the private sector develops its plans for profit maximization, government formulates tourist policy, which is also a matter of public policy. Therefore, tourist policy is a service-oriented policy; a significant amount of input from many sources is a prerequisite for tourism policy. This article explores the conditions and policy practices in the tourist sector using secondary data. Tourists might experience pleasure in Nepal, which is a mysterious location. A more legal structure is required for managing unusual objects.